ANALISIS LOWER EXPLOSIVE LIMIT (LEL) DI KAWASAN PERUMAHAN KORPRI BALIKPAPAN SELATAN - Bambang Sugeng; Ain Sahara; Nurjanah Nurjanah; Faris Aiman; Mohammad Lutfi (PETROGAS: Journal of Energy and Technology, 2023)
Knowledge of explosion thresholds is essential to ensure a safe area. Fire or explosion may occur spontaneously if conditions in the area exceed the limits. Low explosive limit (LEL) measurements for 31 days have been carried out at Korpri Housing, precisely at Jl. Wilis Mukti 1, RT. 26, Kelurahan Sepinggan, Kecamatan Balikpapan Selatan, Balikpapan City, East Kalimantan. Measurements were conducted using a multimeter gas detector (compound gas monitor WT8811) for 31 days at three points, namely the first point was located about 5 m from the gas source, the second point was located at the gas source, and the third point was located around 20-25 m from the gas source. The measurement results revealed that the highest LEL value was at the second point with an average value of 4.79% LEL. The highest measurement results occurred on April 6, 2021 with measurement results in the morning at 09.00 WITA 14.8% LEL, afternoon at 12.00 WITA 13.8% LEL, and at 15.00 WITA 11.6% LEL. The results revealed that at the second point has the highest potential for an explosion.